Florida Crop/Pest Management Profiles: Tomatoes - Mark Mossler; Michael J. Aerts; O. Norman Nesheim (EDIS)
This document is CIR 1238, one of a series of the Pesticide Information Office, Horticultural Sciences Department, UF/IFAS Extension. Published: April 1999. Revised: March 2006.